ANALISA KEUNTUNGAN PETERNAK SAPI POTONG DALAM PROGRAM INSEMINASI BUATAN DI KECAMATAN SELEBAR KOTA BENGKULU - Yossie Yumiati; Heri Dwi Putranto; Rika Dwi Yulihartika (UNIVED Press, Universitas Dehasen Bengkulu, 2015)
Considering the low productivity of Indonesia’s ruminant management, the government proposed Artificial Insemination program as one solution to enhance ruminants productivity. The purpose of this study was to evaluate the economical aspect by using a profit analysis on artificial insemination program in District of Selebar, Bengkulu city. The research was conducted during June to August 2015. There were 4 villages (Pekan Sabtu, Betungan, Bumi Ayu and Sumur Dewa) with total of 70 interviewees. Primary and secondary data were qualitatively and quantitatively analyzed. The profit and total cost were calculated. The results showed that the profit was IDR 8,073,679 (gained fromcarcass sale), the average of revenue was IDR 10,671,429 and the average of cost was IDR 2,597,750.Keywords: Artificial Insemination Program, District of Selebar, Profit, Ruminant.